A Scientometric Review of Global Altmetrics Research. Issue 3 (3rd July 2021) - Nath, Amit; Jana, Sibsankar
ABSTRACT: Altmetrics is considered as an emerging field of research in metrics-based studies and related areas. The main objective of this study was to explore the Scopus database and discover the research publications made on altmetrics over the last eight years and quantify its performance on a global scale. Based on Scopus from 2012 to 2019, a scientometric analysis based on 724 scientific publications related to altmetrics research was done to characterize the scientific landscape by analyzing and identifying the global trends, research power, collaboration network, and core research areas in this field. The results show that the number of publications in altmetrics research has rapidly increased over time and the publication pattern in its developing stage; Scientometrics is the most productive journal and Thelwall, M. is the leading researcher. The maximum number of publications come from the USA and UK, with the University of Wolverhampton being the key organization that performed such research. Researchers mainly preferred journal articles to communicate their research findings with peers. Besides, the keyword analysis shows that "altmetrics, " "bibliometrics, " and "social media" are the frequently used terms used by scholars, which indicates a research focus on these topics.